Limit cycles of discontinuous piecewise differential systems formed by linear centers in R2 and separated by two circles. (August 2021) - Anacleto, Maria Elisa; Llibre, Jaume; Valls, Claudia; Vidal, Claudio
Abstract: We show that discontinuous planar piecewise differential systems formed by linear centers and separated by two concentric circles can have at most three limit cycles. Usually is a difficult problem to provide the exact upper bound that a class of differential systems can exhibit. Here we also provide examples of such systems with zero, one, two, or three limit cycles.